Extracción acuosa y secado del mucilago de Yausabara (Pavonia sepium A. St-Hil - Chillagana Pumashunta, Evelin Maga (2019)
The principal objective of this research work is to evaluate getting mucilage process from MUCILAGENOUS PLANT extraction (Yausaba) (Pavonia sepium A. St.-Hil.), which one is placed on wet grounds. The objective appears from the necessity to improve and develop strategies for agroindustry area. The watery extraction was done to stem peeled cut up and ground with solid and liquid relation about 1:4 y 1:6, during 6; 12 y 24 hours. The investigators determined the viscosity, turbidity that the products have. A treatment called corrida was successful gotten with the extraction of stem peeled it gave a relation solid and liquid 1:4 for about 20, 42 h). It gave as a viscosity result of 51, 72; turbidity of 2600 NTU and total solids of 0, 87%. The mucilage was precipitated with ethanol from an aqueous product, after to the dry process to 40 ºC in a stove for about 3. The powder was the product and it has and antioxidant property and polyphenols using the Fooling–Ciocalteu methods and FRAP respectively. The powder mucilage has a poliphenols contents 0, 0046 mg/g and an antioxidant property expressed as Fe2+, de 18, 63 µM/g that is less than other products from vegetable origin